(untitled) (European Journal of Behavioral Sciences, 2023)
This study investigated the impact of various psychosocial factors on behaviours and attitudes towards cosmetic surgery among Canadian (n=97) and German (n=115) women, considering cultural differences and beauty standards. The primary objective was to provide valuable insights for physicians and psychologists when selecting suitable candidates for elective procedures, as current pre-surgical assessments often fail to integrate the psychological perspective. A correlation analysis was undergone and revealed that neuroticism moderately influenced interest and motivation for cosmetic surgery in both populations. Additionally, the Canadian group exhibited a moderate negative correlation between motivation for cosmetic surgery and early sexual experiences, effectively destigmatizing cosmetic surgery as a social indicator of early sexual behaviours. However, this correlation was not observed in the German cohort. Notably, Canadians reported a higher overall motivation for undergoing cosmetic surgery compared to Germans, as confirmed by a t-test. Surgeons should inquire about sexuality and personality in pre-surgical consultations to determine candidates who may benefit from the procedure and minimize harm. Future research should develop a standardized test for replication and include diverse demographics.